Sistema NPPC-NPR2 na espécie bovina: identificação em folículos antrais e modulação na concentração de nucleotídeos cíclicos e na expressão gênica de PDE3 em complexos cumulus-oócito - Pioltine, Elisa Mariano [UNESP] (2015)
In mice, recent studies have demonstrated that the natriuretic peptide precursor C (NPPC) and its type - 2 - receptor (NPR2) are essential for the maintenance of meiosis I arrest in the oocyte. Moreover, paracrine factors secreted by the oocyte such as bone mo rphogenetic protein 15 (BMP15) can modulate this arrest through the expression of the NPR2 gene in cumulus cells of mice. In a recent study in cattle, the bovine follicular fluid (bFF) added to the maturation medium was able to interfere with the oocyte nu clear maturation resulting in higher embryo yield in vitro . However, it is not known what factors present in bFF might be responsible for this effect and one candidate could be the presence of microvesicles in the bFF. Additionally, the estradiol hormone i s component of the bFF and was demonstrated to directly stimulate NPR2 expression. Therefore, the objectives of this work includes the investigation of the NPPC - NPR2 system in the bovine ovary and the assessment of the effects of exogenous NPPC, estradiol and extracellular vesicles on the expression of the PDE3 gene in bovine oocytes and the concentrations of cyclic - nucleotides in cumulus - oocyte complexes. We designed four experiments: 1) enzyme - linked immunosorbent assay (ELISA) for the presence and concen tration of the NPPC in follicular fluid, in the lysate of mural granulosa cells and in the extracellular vesicles, according to follicular diameter (3 to 6 mm, 6 to 8 mm, >8 mm); 2) Immunolocalization of NPR2 receptor in bovine antral follicles; 3) PDE3 ge ne expression in bovine oocyte by RT - PCR in real time, in immature COCs and in COCs in vitro matured for 6 h with exogenous NPPC, estradiol and extracellular vesicles; 4) Measurement of the concentration of cAMP and cGMP in oocytes and cumulus cells, respectively, either immature or matured in vitro for 6 h with exogenous NPPC or extracellular vesicles through specific...